2011
DOI: 10.1128/aem.06165-11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Detection and Quantification of Botulinum Neurotoxin Type E Activity in Avian Blood

Abstract: Botulinum neurotoxin serotype E (BoNT/E) outbreaks in the Great Lakes region cause large annual avian mortality events, with an estimated 17,000 bird deaths reported in 2007 alone. During an outbreak investigation, blood collected from bird carcasses is tested for the presence of BoNT/E using the mouse lethality assay. While sensitive, this method is labor-intensive and low throughput and can take up to 7 days to complete. We developed a rapid and sensitive in vitro assay, the BoTest Matrix E assay, that combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…Como desventajas, hay que utilizar animales de laboratorio y exige la utilización de pruebas de neutralización para la determinación del serotipo de toxina 62 . Existen otras pruebas alternativas que tienen similar sensibilidad y confiabilidad 104 , como las técnicas de radioinmunoensayo, inmunoprecipitación, hemaglutinación pasiva y ELISA 12,20,75,76 . También se han desarrollado varias metodologías de reacción en cadena de polimerasa (PCR) para optimizar el diagnóstico sin utilizar animales de laboratorio 25,40,48,77 .…”
Section: Diagnósticounclassified
“…Como desventajas, hay que utilizar animales de laboratorio y exige la utilización de pruebas de neutralización para la determinación del serotipo de toxina 62 . Existen otras pruebas alternativas que tienen similar sensibilidad y confiabilidad 104 , como las técnicas de radioinmunoensayo, inmunoprecipitación, hemaglutinación pasiva y ELISA 12,20,75,76 . También se han desarrollado varias metodologías de reacción en cadena de polimerasa (PCR) para optimizar el diagnóstico sin utilizar animales de laboratorio 25,40,48,77 .…”
Section: Diagnósticounclassified
“…As enzymatic assays, endopeptidase assays are relatively sensitive toward changes in reaction conditions, and testing of complex matrices can dramatically affect assay performance (Rasooly and Do 2008;. To reduce matrix interference, an immunoaffinity enrichment step has been introduced, where the toxin is captured from the matrix using antibody-coated magnetic microbeads prior to performing the endopeptidase reaction, resulting in assay sensitivities similar to those of the MBA (Wictome et al 1999a, b;Rasooly and Do 2008;Piazza et al 2011). Immunoaffinity enrichment is advantageous since it separates the toxin from other proteases which might cleave the SNARE peptide unspecifically, preventing false-positive results.…”
Section: Endopeptidase Assaysmentioning
confidence: 99%
“…Some of the discrepancies can be explained by the fact that SNAP-25 is not only bound around the active site of BoNT, but also by so-called a-and b-exosites upstream and downstream of the active site (Breidenbach and Brunger 2004;Brunger et al 2008;Henkel et al 2009). With respect to assay conditions, it has been shown that certain buffer components such as NaCl can reduce or even abolish cleavage of SNAP-25 or VAMP (Ferracci et al 2011;Jones et al 2011;Piazza et al 2011).…”
Section: Endopeptidase-mass Spectrometry (Endopep-ms) Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In fluorescence-based methods, a pair of fluorescence donor and acceptor molecules is incorporated into the peptide substrate. The presence and activity of botulinum neurotoxin is detected by monitoring the fluorescence of the toxin cleavage products using fluorescence resonance energy transfer technology (FRET) (Schmidt and Stafford 2003;Dong, Tepp et al 2004;Rasooly and Do 2008;Gilmore, Williams et al 2011;Piazza, Blehert et al 2011). An in vitro assay (ALISSA) using a large immune-sorbent surface area for toxin capture and enrichment and a fluorogenic peptide substrate for activity measurement has been reported recently and high sensitive detection of BoNTs in complex biological matrices can be achieved by this method (Bagramyan, Barash et al 2008;Bagramyan and Kalkum 2011).…”
Section: Introductionmentioning
confidence: 99%